Resistance of old winter bread wheat landraces to tan spot - N. V. Mironenko; N. M. Kovalenko; O. A. Baranova; O. P. Mitrofanova (Труды по прикладной ботанике, генетике и селекции)
Background. The most effective and environmentally safe way to combat wheat diseases is to produce cultivars resistant to their pathogens. For this purpose, old landraces are often used as genetically diverse sources of traits important for breeding. In the process of wheat breeding for resistance to tan spot caused by the fungus Pyrenophora tritici-repentis (Died.) Drechs. (abbr. Ptr), selection is carried out against the dominant allele of Tsn1, the gene of sensitivity to the toxin Ptr ToxA, which induces necrosis and represents the main pathogenicity factor of Ptr controlled by the ToxA gene. The aim of the study was to characterize a set of bread wheat (Triticum aestivum L.) accessions from the VIR collection for resistance to various Ptr populations, genotype these accessions using Xfcp623 – a DNA marker of the Tsn1 gene, and identify sources of tan spot resistance.Materials and methods. Sixty-seven accessions of winter bread wheat landraces were studied. Seedling resistance to two Ptr populations was assessed using a 5-point scale adopted at VIZR. The allelic state of Tsn1 was identified by PCR.Results. Dominant alleles of Tsn1 were found for 55% of the studied accessions. Seventeen accessions were resistant or moderately resistant to two Ptr populations and an isolate from Krasnodar Territory previously used for their characterization. Nine of them had the tsn1tsn1 genotype, and 8 had Tsn1Tsn1. The accessions mainly belonged to three agroecological groups proposed by N. I. Vavilov: “steppe winter bread wheat (Banatka wheats)”, “North European forest awnless bread wheats (Sandomirka wheats)”, and “Caucasian mountain winter bread wheat”.Conclusion. The identified 17 accessions resistant to Ptr are potential breeding sources of resistance. In the studied set of accessions, no significant relationship was found between the allelic state of the Tsn1 gene in the accession and its response to the infection with pathogen populations, including isolates with the ToxA gene.